New Findings for the Composition and Structure of Ni Nanoparticles Protected with Organomercaptan Molecules - Calderón Segovia, Matías Francisco (2013)
Here we explore the synthesis of alkanethiolcoated Ni NPs following the one-phase reaction method by Brust et al.1 The reduction of NiCl2 with NaBH4 in the presence of dodecanethiol (C12SH) yields a complex product that is difficult to identify as illustrated in the figure of merit. We synthesized Ni(II) dodecanethiolate (C12S) (without the addition of NaBH4) for comparison and performed an exhaustive characterization with TEM, HR-TEM, AFM, MFM, XPS, XRD, UV−vis, magnetism, and FT-IR. It is found that the organic coating is not quite a well-organized self-assembled monolayer (SAM) surrounding the Ni cluster as previously reported.2,3 XPS and XRD data show slight differences between both syntheses; however, Ni(II) thiolate appears to be more stable than reduced Ni when exposed to ambient air, indicating the propensity of metallic Ni to oxidize. It has been shown that irradiating with TEM electrons over various metal thiolates leads to nanoparticle formation.4 We irradiated over Ni(II) thiolate and observed no evidence of NP formation whereas irradiating a reduced Ni sample exhibited an ∼3.0 nm nanoparticle diameter. Magnetism studies showed a difference between both samples, indicating ferromagnetic character for the reduced Ni sample. According to our results, the product of the synthesis is comprised of ultrasmall metallic clusters embedded in some form of Ni(II) C12S. In this work, we open a discussion of the chemical nature of the core and the shell in the synthesis of Ni NPs protected with organomercaptan molecules.